ETHICAL ASPECTS OF APPLICATION THE GENOMIC MEDICINE IN SPORT - Biljana Vitošević; Nebojša R. Mitić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Today's level of knowledge of molecular biology and genetics is able to change the established belief that genetic predisposition is a good natural gift. The application of gene therapy in healthy individuals in order to increase sports performance is considered as manipulation and gene doping, which is actually believed that it could be a precursor to a broader notion of human "genetic enhancement" of physical characteristics such as strength, intelligence, social behavior and general improving the quality of life by genetic make-ap. In this sense, gene doping can have a significant and long-term impact on health and society in general and requires a more detailed ethical analysis and the implementation of preventive measures. The paper discusses the manipulation of genomic medicine in sport in terms of basic ethical principles and represents academic contributions to the study of the prevention, detection and control of this type of doping. Sport can and should keep the leading position in the scale of moral values in society through ethical arguments based on the balance of equality, rights and responsibilities. We cannot prevent the evolution of the sport, but we can and must direct this evolution in a better direction.